2011
DOI: 10.1038/ng.784
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale association analysis identifies 13 new susceptibility loci for coronary artery disease

Abstract: We performed a meta-analysis of 14 genome-wide association studies of coronary artery disease (CAD) comprising 22,233 cases and 64,762 controls of European descent, followed by genotyping of top association signals in 60,738 additional individuals. This genomic analysis identified 13 novel loci harboring one or more SNPs that were associated with CAD at P<5×10−8 and confirmed the association of 10 of 12 previously reported CAD loci. The 13 novel loci displayed risk allele frequencies ranging from 0.13 to 0.91 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

51
1,502
14
11

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 1,736 publications
(1,591 citation statements)
references
References 39 publications
51
1,502
14
11
Order By: Relevance
“…We also examined the associations of the IGF‐I‐ and IGFBP‐3‐associated SNPs with anthropometric traits (height, BMI, waist‐to‐hip ratio, and fat percentage) (Heid et al ., 2010; Lango Allen et al ., 2010; Speliotes et al ., 2010), bone mineral density (Estrada et al ., 2012), risk of type 2 diabetes (Voight et al ., 2010; Morris et al ., 2012) and related traits (fasting glucose, 2‐h glucose, HbA1c, fasting insulin, proinsulin, HOMA‐IR, and HOMA‐B) (Dupuis et al ., 2010; Saxena et al ., 2010; Soranzo et al ., 2010), and coronary artery disease (Coronary Artery Disease Genetics C, 2011; Schunkert et al ., 2011; Consortium CAD and Deloukas, 2013) (Table S9, Supporting information). Many nominal associations were expected because of the known influence of the IGF system on these traits.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also examined the associations of the IGF‐I‐ and IGFBP‐3‐associated SNPs with anthropometric traits (height, BMI, waist‐to‐hip ratio, and fat percentage) (Heid et al ., 2010; Lango Allen et al ., 2010; Speliotes et al ., 2010), bone mineral density (Estrada et al ., 2012), risk of type 2 diabetes (Voight et al ., 2010; Morris et al ., 2012) and related traits (fasting glucose, 2‐h glucose, HbA1c, fasting insulin, proinsulin, HOMA‐IR, and HOMA‐B) (Dupuis et al ., 2010; Saxena et al ., 2010; Soranzo et al ., 2010), and coronary artery disease (Coronary Artery Disease Genetics C, 2011; Schunkert et al ., 2011; Consortium CAD and Deloukas, 2013) (Table S9, Supporting information). Many nominal associations were expected because of the known influence of the IGF system on these traits.…”
Section: Resultsmentioning
confidence: 99%
“…Top SNPs associated with levels of IGF‐I and IGFBP‐3 were examined in relationship to other phenotypes using published data on serum metabolites (Suhre et al ., 2011; Shin et al ., 2014), anthropometric traits (Heid et al ., 2010; Lango Allen et al ., 2010; Speliotes et al ., 2010), bone mineral density (Estrada et al ., 2012), diabetes (Voight et al ., 2010; Morris et al ., 2012) and glycemic traits (Dupuis et al ., 2010; Saxena et al ., 2010; Soranzo et al ., 2010), coronary artery disease (Coronary Artery Disease Genetics C, 2011; Schunkert et al ., 2011; Consortium CAD and Deloukas, 2013), and survival beyond 90 years (Broer et al ., 2015). Detailed information of the published datasets used including its references is given in Table S9 (Supporting information).…”
Section: Methodsmentioning
confidence: 99%
“…The joint forces of the CARDIoGRAM (Schunkert et al , 2011), C4D (Coronary Artery Disease C4D Genetics Consortium, 2011) and finally the CARDIoGRAMplusC4D (CARDIoGRAMplusC4D Consortium et al , 2013; Nikpay et al , 2015) consortium allowed the analysis of up to 180,000 individuals, about half of which had CAD. Interestingly, consequent studies revealed a strong relationship between the numbers of individuals investigated and the numbers of genome‐wide significant variants detected by the GWAS approach (Fig 1).…”
Section: Genome‐wide Association Studies In Coronary Artery Disease Amentioning
confidence: 99%
“…(B) The number of SNP s detected with genome‐wide significance after replication correlates with the number of individuals included in the discovery studies. Symbols denote the numbers of genotyped SNP s [dots: ≤ 500,000 SNP s (Samani et al , 2007; McPherson et al , 2007; Helgadottir et al , 2007; Myocardial Infarction Genetics Consortium, 2009; Erdmann et al , 2009; Tregouet et al , 2009; IBC 50K CAD Consortium, 2011; Lu et al , 2012); asterisks: 2,500,000 SNP s (Coronary Artery Disease C4D Genetics Consortium, 2011; Schunkert et al , 2011; CARDIoGRAMplusC4D Consortium et al , 2013); arrow: 940,000 SNP s (Nikpay et al , 2015)].…”
Section: Genome‐wide Association Studies In Coronary Artery Disease Amentioning
confidence: 99%
See 1 more Smart Citation